Relationship of chronic rhinosinusitis with dental malocclusion: a prospective study - Sonone, Jayant K.; Tikar, Gaurav S.; Thakare, Pallavi G.; Meshram, Sushil N. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The purpose of this study was to find the effect of chronic rhinosinusitis on dental malocclusion. A malocclusion is defined as an irregularity of the teeth or a mal relationship of the dental arches beyond the range of what is accepted as normal. Malocclusion may not be life-threatening, but it is an important public health issue as it compromises the health of oral tissues and also can lead to psychological and social problems. There are numerous studies in the literature about prevalence of the dental malocclusion but there is no study regarding association of CRS and malocclusion. Several factors related to malocclusion, such as anterior crowding, midline malalignment, and facial asymmetry, have strong effects on the perception of facial aesthetics, which influence the psychological development and in turn, influence social acceptance and self‑perception. Methods: This was a prospective cross-sectional observational study was conducted from September 2015 to August 2017 and 57 patients with diagnosis of having chronic sinusitis, were evaluated for dental occlusion. Malocclusion is then classified by angle’s classification. Results: Most patients of chronic rhinosinusitis had dental malocclusion in grade II, followed by grade I, then grade III. Conclusions: While treating the patients of CRS one must keep in mind that he may have class II malocclusion which may cause gum disease, poor oral hygiene, impaired speech, mastication and aesthetics of face and need orthodontics management as well.